Poland and Russia at the turn of XXI century. Between a Liberal Illusion and Imperial Realism - Adriana Dudek (Revista UNISCI, 2016)
In this article the author examines how Poland and Russia perceive international relations and the objectives of foreign policy using specific research approaches. Later, the article tries to illustrate the incompatibility of the ways these two countries perceive the world. In order to achieve this goal, it was necessary to refer to concepts explaining these two approaches. In this regard, the author takes advantage of selected currents of structural and offensive realism, the concept of interdependence, institutionalism and liberal theory, which in the context of identification of preferences and perceptions were complemented by research reflections originating in constructivism.